Antipsychotic Drugs Predominate in Pharmacotherapy of Nursing Home Residents with Dementia - Huber, M.; Kölzsch, M.; Rapp, M. A.; Wulff, I.; Kalinowski, S.; Bolbrinker, J.; Hofmann, W.; Scholze, J.; Dräger, D.; Kreutz, R. (Pharmacopsychiatry, 2012)
The aim of this study was to investigate the frequency of benzodiazepines, antidementia and antipsychotic drug prescriptions in nursing home residents (NHR).Data of a German health insurance company were retrospectively analyzed for the year 2008.The study cohort comprised 13 042 NHR (82% women, mean age 83.6±7 years). Following analgetics, antipsychotic drugs were the second most frequently prescribed drug group with 13.3% of all prescriptions. Dementia was diagnosed in 8 017 (61.5%) NHR. Thereof 51.6% received an antipsychotic, 17.3% a benzodiazepine and 15.2% an antidementia pharmaceutical, respectively. 18.1% of NHR with dementia and antipsychotic drug prescriptions were in combined treatment with antidementia pharmaceuticals. The rate of antipsychotic drug prescribing was significantly doubled in NHR with dementia compared to those without this diagnosis (p<0.01); the most frequently prescribed antipsychotics were melperone, risperidone and pipamperone.This study demonstrates the wide-spread use of psychotropic drugs in NHR. Moreover, dementia in NHR was associated with antipsychotic drug prescribing in every second patient. This highlights the need for further studies analyzing alternative treatments for dementia-related symptoms.
Keywords: dementia; antipsychotic drugs; anti-dementia drugs; nursing home residents; elderly